2017
DOI: 10.3390/brainsci7110144
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder and Immune Dysfunction: Epidemiological Findings, Proposed Pathophysiology and Clinical Implications

Abstract: Bipolar disorder (BD) is strongly associated with immune dysfunction. Replicated epidemiological studies have demonstrated that BD has high rates of inflammatory medical comorbidities, including autoimmune disorders, chronic infections, cardiovascular disease and metabolic disorders. Cytokine studies have demonstrated that BD is associated with chronic low-grade inflammation with further increases in pro-inflammatory cytokine levels during mood episodes. Several mechanisms have been identified to explain the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(147 citation statements)
references
References 144 publications
(187 reference statements)
4
141
0
2
Order By: Relevance
“…Whether these immunity-related mechanisms play a role in the mood stabilizing effects of lithium remains to be determined. Immune components of psychiatric illness including BD 57 have long been recognized, but it remains unclear if they represent a causal pathway, a property of the disease state, or a consequence of environmental factors like body mass index or smoking. These results contribute to the understanding of the genomics of lithium action, which may be essential for the future of personalized psychiatric medicine for patients with BD.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these immunity-related mechanisms play a role in the mood stabilizing effects of lithium remains to be determined. Immune components of psychiatric illness including BD 57 have long been recognized, but it remains unclear if they represent a causal pathway, a property of the disease state, or a consequence of environmental factors like body mass index or smoking. These results contribute to the understanding of the genomics of lithium action, which may be essential for the future of personalized psychiatric medicine for patients with BD.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, TNF levels increase, and sustained TNF elevation and dysregulation have been implicated in the development of autoimmune diseases, including rheumatoid arthritis and Crohn's disease . Interestingly, autoimmune diseases share significant comorbidity with mood disorders, to an extent that cannot be explained by chance . Furthermore, both severe infection and autoimmune disease have been cited as risk factors for the development of depressive symptoms; in particular, repeated infections have been shown to be associated with an increase in the likelihood of the onset of depressive symptoms …”
Section: Tnf Abnormalities In Mood Disordersmentioning
confidence: 99%
“…31 Interestingly, autoimmune diseases share significant comorbidity with mood disorders, to an extent that cannot be explained by chance. [32][33][34] Furthermore, both severe infection and autoimmune disease have been cited as risk factors for the development of depressive symptoms; 34,35 in particular, repeated infections have been shown to be associated with an increase in the likelihood of the onset of depressive symptoms. 35 Currently, studies in the periphery provide the strongest link implicating TNF in the pathophysiologies of mood disorders, with these data arguing a relationship between immune-related dysfunction and mood disorder pathology.…”
Section: Tnf Abnormalities In Mood Disordersmentioning
confidence: 99%
“…The dysregulation of inflammatory responses has recently been implicated in the neuroimmunopathogenesis of mental disorders, specifically as an etiological factor in disorders such as BPAD, unipolar depression, and schizophrenia [9-17]. A recent study found that patients with bipolar disorder (BD) who are in manic or depressed states have higher levels of circulating, activated T cells and serum interleukin (IL)-2 receptors when compared to healthy controls [18, 19].…”
Section: What Is the Role Of Psychoneuroimmunology In Bpad?mentioning
confidence: 99%